Name, shame and blame : criminalising consensual sex in Papau New Guinea - Stewart, Christine (Legal officer) (ANU Press, 2014)
Papua New Guinea is one of the many former British Commonwealth colonies which maintain the criminalisation of the sexual activities of two groups, despite the fact that the sex takes place between consenting adults in private: sellers of sex and males who have sex with males. The English common law system was imposed on the colonies with little regard for the social regulation and belief systems of the colonised, and in most instances, was retained and developed post-Independence, regardless of the infringements of human rights involved.
Keywords: Sexual consent -- Social aspects -- Papua New Guinea.; Prostitution -- Social aspects -- Papua New Guinea.; Prostitution -- Law and legislation.; Homosexuality -- Law and legislation -- Papua New Guinea.; Homosexuality -- Social aspects -- Papua New Guinea.; Papua New Guinea -- Social conditions.; Ethical issues: prostitution & sex industry.; Gay studies (Gay men); Social Science / Sociology.; Homosexuality -- Law and legislation.; Homosexuality -- Social aspects.; Prostitution -- Social aspects.; Social conditions.; Papua New Guinea.; papua new guinea.; pacific.; hiv.; sex.; criminalisation.; Electronic books.